Avaliação da toxicidade in vitro e in vivo de moléculas potencialmente terapêuticas - Daniela Rodrigues Tonholo (2018)
In the development of new medicines, nine out of ten promising candidates entering the clinical phase will not receive approval. Reducing the failure of drug candidates using in vitro assays can reduce the unnecessary use of animals as well as predict toxic effects at preclinical stages. The objective of the present study was to evaluate MTT cytotoxicity of four new substances in the A549, H9C2, HEP-G2, LLC-PK1 and NEURO-2 cell lines. For the substance that showed the lowest cytotoxicity in the MTT test, the neutral red test according to OECD 129 was performed in order to extrapolate the result obtained as the initial dose for the acute toxicity test (OECD 423). An initial dose of 300 mg / kg did not promote observable toxic effects for the animals studied. On the other hand, the dose of 2000 mg / kg resulted in the death of one animal in each group; however, none of the groups presented macroscopic changes at necropsy. The results of the present study shows limitations of the neutral red test as a predictor of the initial dose for the acute toxicity study due to several factors such as limited in vivo bioavailability and generation of toxic metabolites.